MENINGKATKAN KEMAMPUAN MOTORIK HALUS PADA ANAK USIA 5-6 TAHUN MELALUI MENGANYAM DI TK ISLAM TERPADU AL - IZZAH KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Handayani, Yayuk; Chairilsyah, Daviq; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this research is lacking increasing children's ability to fine motor skills, some children may not be able to stick with the right image, to explore the various media and activities, some children may not be able to use the stationery properly and some children may not be able to advantageous according to the pattern. THEREFORE, the need to increase the fine motor skills of children, namely: through weaving. the purpose of this study was to determine whether there is an increase in the fine motor skills of children through weaving activities and to determine how the increase that occurred. This type of research is classroom action research done in 2 cycles. data collection tool used in this study is in the form of observation sheet. the number of samples in this study were 10 children consisting of 4 boys and 6 girls. Based analysis of the assessment process there was an increase of 2 cycles. a spike that of prior actions amounted to 34.88% cycle 1, cycle I to cycle II is 43.37%, and increased from the first cycle to the second cycle of 93.35%. from these results we can conclude that through the activities of weaving can improve fine motor skills in children aged 5-6 years in kindergarten Isam Al-Izzah District of Bangko.Keyword: Fine Motor, Weaving